The Indirect Impact of Overconfidence on the Performance of Tunisian Firms Through their Financing Structure - Dahmani, Manel; Zouari, Ghazi (Financial Risk and Management Reviews, 2016)
In the current framework of behavioral corporate finance, this article studies the relationship between the managers’ overconfidence and firm performance through the financing structure in the Tunisian context. Our model seeks to identify if the financing structure as a mediating variable between the performance and overconfidence. The empirical study is based on a sample of 56 firm managers for the year 2014. The results of the conducted regressions confirm the existence of a mediating effect of the financing structure on the relationship between overconfidence and the performance of Tunisian firms.